UPAYA GREENPEACE DALAM MENGURANGI KEBAKARAN HUTAN YANG TERJADI DI INDONESIA PADA TAHUN 2015 - 2017 - Firdha Amalia, (2020)
Forests are an important asset in life where forests produce oxygen and maintain ecosystems. Indonesia as a country with vast tropical forests where each of these forests is stored diverse natural and biological wealth. The event of forest fires in Indonesia every year becomes an inevitable problem, where such events often become international talks. Greenpeace as one of the Non-Government organizations under the auspices of the United Nations which focuses on the environment, came to Indonesia to monitor forests in Indonesia. As an organization that cares about the environment, Greenpeace has made various efforts to reduce forest fires that occur in Indonesia. This study uses a qualitative approach in which the type of research is descriptive. The sources used in this study come from literature studies and observations made on documents, journals, and reports. Data were analyzed using Green Theory. Based on the data analysis conducted, it was concluded that Greenpeace carried out campaigns and cooperation in reducing fires that occurred in Indonesia, where the fire could create a global problem. Keywords : Greenpeace, Fires, Forest, Indonesia.